MacroD1 Is a Promiscuous ADP-Ribosyl Hydrolase Localized to Mitochondria - Agnew, Thomas; Munnur, Deeksha; Crawford, Kerryanne; Palazzo, Luca; Mikoč, Andreja; Ahel, Ivan (Frontiers in Microbiology, 2018)
MacroD1 is a macrodomain containing protein that has mono-ADP-ribose hydrolase enzymatic activity towards several ADP-ribose adducts. Dysregulation of MacroD1 expression has been shown to be associated with the pathogenesis of several forms of cancer. To date, the physiological functions and sub-cellular localization of MacroD1 are unclear. Previous studies have described nuclear and cytosolic functions of MacroD1. However, in this study we show for the first time that endogenous MacroD1 protein is highly enriched within mitochondria. We also show that MacroD1 is highly expressed in human and mouse skeletal muscle. Furthermore, we show that MacroD1 can efficiently remove ADP-ribose from 5’ and 3’-phosphorylated double stranded DNA adducts in vitro. Overall, we have shown that MacroD1 is a mitochondrial protein with promiscuous enzymatic activity that can target the ester bonds of ADP-ribosylated phosphorylated double-stranded DNA ends. These findings have exciting implications for MacroD1 and ADP-ribosylation within the regulation of mitochondrial function and DNA-damage in vivo.